Mullite whiskers grown in situ reinforce a pre-ceramic resin adhesive for silicon carbide ceramics. Issue 8 (1st June 2019) - Wang, Mingchao; Li, Lingyu; Li, Zhiyun; Du, Mingrun; Liu, Jiachen; Zhou, Qingjun; Feng, Zhaojie
Abstract: Mullite whiskers were successfully synthesized in situ in a pre-ceramic silicone resin adhesive by using AlF3 as a catalytic initiator. Through a VS reaction mechanism, a small number of short and thin mullite whiskers formed at 900 °C, gradually grew into needle-like whiskers at 1300 °C, and finally became long wires at 1500 °C. Combined with the formation of high-temperature-resistant ceramics, the strength and the fracture toughness of the whisker-grown adhesive was greatly improved after calcination at 1300 °C and increased by 90.6% and 109%, respectively. The bonding strength of the joint calcined at 1300 °C was enhanced to a maximum of 49 MPa, and a characteristic clear zigzag waveform appeared in the load-displacement curve that was attributed to the synergy of the whisker drawing, pull-out, and bridging mechanisms.